Robust Increases of Land Equivalent Ratio with Temporal Niche Differentiation: A Meta‐Quantile Regression - Yu, Yang; Makowski, David; Stomph, Tjeerd‐Jan; Werf, Wopke (Agronomy journal, 2016)
Intercropping has been shown to be land use efficient, but there is a large variation in the land equivalent ratio (LER) among studies. We used quantile regression to estimate the effect of temporal niche differentiation and its interaction with other key characteristics of intercropping, i.e., crop type combination, N fertilizer, relative density, and intercropping pattern, using data from the intercropping literature. Quantile regression characterizes the entire distribution of the response metric by estimating quantiles of this distribution. This method gives a comprehensive characterization of the diversity of the response in the population. In this study, the effect of temporal niche differentiation on the LER was positive and significant across all quantiles (10, 15, …, 85, 90%). The response of the LER to temporal niche differentiation was similar in C3–C3 and C3–C4 intercrops except at low quantiles (below 20%), where a stronger response was found in C3–C4 than in C3–C3 intercrops. There was a negative effect of N fertilizer on the LER in the absence of temporal niche differentiation at all tested quantiles. At low LER (quantiles <20%), this negative effect was alleviated by increasing temporal niche differentiation due to a positive interaction between N fertilizer and temporal niche differentiation. The results indicate that temporal niche differentiation has a robust positive effect on the LER across a wide range of LERs, but the strength of this effect is influenced by intercrop characteristics, especially at low to median LER values. Case‐specific experiments are therefore indispensable for identifying advantageous species mixtures and optimal management adapted to local conditions. Core Ideas Land equivalent ratio (LER) of intercrops increases with temporal niche differentiation (TND). The positive effect of TND on LER is robust across a wide range of LER. At lower LER, the effect of TND is stronger in C3–C4 than C3–C3 intercrops. N fertilizer amount interacted negatively with TND but only at lower LER. Quantile regression complemented insights obtained with ordinary regression.